2016
DOI: 10.1002/2016jd025063
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of eddy covariance measurements in Basel, Switzerland: Seasonal and interannual variabilities of urban CO2 mole fraction and flux

Abstract: Eddy covariance (EC) measurements of carbon dioxide (CO2) in urban environments are carried out widely since the late nineties. However, long‐term time series are still rare and little is known about long‐term tendencies, even though cities are major sources of CO2 globally. Here a full decade of EC measurements from Basel, Switzerland, is presented. An approach for the calculation of horizontal averages is presented. It improves the significance and comparability of measured fluxes from heterogeneous environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
(75 reference statements)
3
18
0
Order By: Relevance
“…6.39 g CO 2 m -2 day -1 ) and higher [CO 2 ] (+49.38 ppm). The only previous study with a large low-rise structure was found in Houston, USA [81], which reported a higher daily value (29.38 g CO 2 m -2 day -1 ) during the summer, however, other highly urbanized sites including compact low-rise [13,38,39,53], compact mid-rise [12,24,48,59,[82][83][84][85][86] and compact high-rise [50], reported values between 18.7 and 71.7 g CO 2 m -2 day -1 during the summer. The Pearson correlation coefficient (CC) of FC between XL and PL and REF was significant (CC = 0.31 and 0.37, respectively), whereas ML had a much lower, insignificant correlation (CC = -0.15), Carbon dioxide fluxes in Phoenix, Arizona suggesting a stronger similarity in the factors affecting FC at these two sites (see Table 4 for a comparison of CC for other variables between the mobile deployments and REF site [59], Saint Paul, USA [87], and Montreal, Canada [30].…”
Section: Seasonal Variations In Meteorological and Co 2 Conditionsmentioning
confidence: 92%
See 1 more Smart Citation
“…6.39 g CO 2 m -2 day -1 ) and higher [CO 2 ] (+49.38 ppm). The only previous study with a large low-rise structure was found in Houston, USA [81], which reported a higher daily value (29.38 g CO 2 m -2 day -1 ) during the summer, however, other highly urbanized sites including compact low-rise [13,38,39,53], compact mid-rise [12,24,48,59,[82][83][84][85][86] and compact high-rise [50], reported values between 18.7 and 71.7 g CO 2 m -2 day -1 during the summer. The Pearson correlation coefficient (CC) of FC between XL and PL and REF was significant (CC = 0.31 and 0.37, respectively), whereas ML had a much lower, insignificant correlation (CC = -0.15), Carbon dioxide fluxes in Phoenix, Arizona suggesting a stronger similarity in the factors affecting FC at these two sites (see Table 4 for a comparison of CC for other variables between the mobile deployments and REF site [59], Saint Paul, USA [87], and Montreal, Canada [30].…”
Section: Seasonal Variations In Meteorological and Co 2 Conditionsmentioning
confidence: 92%
“…As an alternative applied in this study, the eddy covariance (EC) method [45] can be used to measure CO 2 fluxes (FC) in urban areas [6,11,12,15,16,30,39,46]. However, urban EC observations have been generally limited, as compared to those efforts in natural ecosystems, with most studies undertaken in very dense urban settings or in open low-density areas of northern latitudes [6,[47][48][49][50][51][52][53]. Furthermore, arid cities have been generally underrepresented in the use of the EC method [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…During all acquisitions, the TCWV did thereby not exceed 2.5 cm and a majority of the scenes was acquired with a TCWV below 1.5 cm. For the atmospheric correction, NCEP reanalysis data accessed via the web-based ACT [56] and improved with in-situ meteorological data from a measurement tower-maintained by the Research Group of Meteorology, Climatology and Remote Sensing of the University Basel (MCR)-is applied [63]. The data is adapted to terrain by the ASTER Global Digital Elevation Model (GDEM).…”
Section: Datamentioning
confidence: 99%
“…These values are projected to the underlying topography using a piecewise cubic interpolation ( Figure 3). Meteorological ground truth data from the measurement station Basel Klingelbergstrasse [63] representing the surface conditions (i.e., relative humidity, air temperature, and pressure) are The climate is considered oceanic, with mild winters and warm and sunny summers (Köppen Cfb climate) [26,66]. The annual mean temperature is 10.5 • C with an annual precipitation rate of 842 mm according to the suburban weather Station Basel/Binningen maintained by the Federal Office of Meteorology and Climatology for the reference period 1981 to 2010 [67].…”
Section: Land Surface Temperaturementioning
confidence: 99%
See 1 more Smart Citation